Experiences and perceptions of dementia in Vietnam and among the Vietnamese diaspora: a systematic review of qualitative studies - Nguyen, Tuan Anh; Tran, Kham Van; Hinton, Ladson; Roughead, Elizabeth E; Esterman, Adrian; Dang, Thu Ha; Kim, Giang Bao; Pham, Diep Bich; Nguyen, Huong Thi Diem; Crotty, Maria; Kurrle, Susan; Pham, Thang; et al. (Aging & mental health, 2023)
Objectives: This paper aimed to review and synthesise the qualitative research evidence on the experiences and perceptions of dementia in Vietnam and among the Vietnamese diaspora. Methods: Systematic searches were conducted in June 2019 using Medline, Embase, Emcare, PsycINFO and Cochrane electronic databases, as well as grey literature. Keywords and Medical Subject Headings [MeSH terms] for dementia and associated terms were combined with keywords for Vietnam and its provinces. Qualitative research articles published in English or Vietnamese were included to examine evidence on the life experiences of Vietnamese people with dementia using thematic analysis. Results: Our searches resulted in 3,940 papers, from which 21 qualitative research studies were included for final analysis. The majority of research has not been undertaken in Vietnam but with the Vietnamese diaspora in Western countries and has taken a cultural perspective to analyses. Research in Western countries has focused on the need for culturally adapted and culturally sensitive models of care. Emerging themes about the life experiences of Vietnamese people with dementia identified from the studies included: many people do not have diagnostic terms for dementia but use the descriptive language of symptoms; stigma was a reported problem and on occasions can be observed in the descriptive language used for people with dementia; cultural and traditional values create both an opportunity and a barrier, supporting compassion, family care and relaxation, but creating barriers to accessing health services or long-term residential care. Conclusions: This is the first systematic review reporting qualitative evidence on the life experiences of people with dementia in Vietnam and among the Vietnamese diaspora. Future research is needed on the voice of people with dementia themselves and their caregivers particularly in Vietnam, and low and middle-income countries with regards to living with dementia, pathways to care from diagnosis, treatment, care and support, additional social care and preparedness for end of life care for people with dementia.